2016
DOI: 10.1177/1043659615587585
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Healthy Lifestyle Behaviors in a Sample of Turkish Adolescents

Abstract: These findings can be used as a guide in developing an adolescent health promotion program for school nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
7
23
2
Order By: Relevance
“…A longitudinal study [51] revealed that receiving high-quality social support can help to lower the risk of future suicidal ideation in female adolescents. By contrast, the female adolescent participants in this study performed relatively poorly in terms of health responsibility behaviors, which is consistent with the results of previous studies [52, 53]. A possible explanation for this is that the adolescent participants were still too young to worry about or pay attention to their health.…”
Section: Discussionsupporting
confidence: 90%
“…A longitudinal study [51] revealed that receiving high-quality social support can help to lower the risk of future suicidal ideation in female adolescents. By contrast, the female adolescent participants in this study performed relatively poorly in terms of health responsibility behaviors, which is consistent with the results of previous studies [52, 53]. A possible explanation for this is that the adolescent participants were still too young to worry about or pay attention to their health.…”
Section: Discussionsupporting
confidence: 90%
“…Given the long time spent by adolescents sitting in school chairs and carrying heavy school backpacks, mechanical reasons are considered the most common cause of pain (Adami et al, 2015;Clinch, 2009;Gouvali et al, 2006;Jackson et al, 2011;Widhe, 2001). A significant portion of the general population spends their lives carrying school backpacks and sitting for a long time during the adolescence period (Ardic et al, 2016;Guler, 2004;Parcells et al, 1999). Several studies have reported incompatibility in the anthropometric features of adolescents and school furniture (Murphy et al, 2007;Panagiotopoulou et al, 2004;Parcells et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The population of 10-to 19-year-old individuals accounts for 25% of the total population in Turkey (Ardic & Esin, 2016;Turkish Statistical Institute, 2013). In other words, one of four individuals in our country spends a significant part of his/her life carrying a school backpack and sitting statically for learning activities at school.…”
mentioning
confidence: 99%
“…In a study by Meydanlıoglu, it was observed that students with healthy food intake are more successful than students who consume sugary foods, salty snacks or fast food in general [9]. Additionally, Ardic and Esin reported that significant predictors of healthy lifestyle behaviors of adolescents, included good relationships with family and friends, having a father who was a college graduate, and good health perception, thus indicating that SES is a predictor of good health and better dietary practices [38]. Furthermore, work by Ardic and Erdogan showed that adolescents in relevant intervention groups showed improvements in nutritional behavior, physical activity and stress management [39].…”
Section: Discussionmentioning
confidence: 99%